FACTORS RELATED TO ADOLESCENT DELAY IN PANEMBONG GIRANG CIANJUR - Helvy Yunida (Bajang Institute, 2021)
The juvenile delinquency rate in Panembong girang has long been very high. The environment is not good. For parents who have teenagers, they will be very worried if their teenagers are released to hang out with teenagers in such an environment. Many behaviors that lead to juvenile delinquency. The teenager's acquaintance with the Panembong Girang teenager has led to a legal case, which has ended at the court. These include being involved in drug abuse, beating other people until they are seriously injured and sentenced to prison, drinking alcohol, promiscuity, stealing, and others. The impact of juvenile delinquency The juvenile mortality rate in Panembong Girang is very high, compared to the death rate of adults and parents. The cause of the high mortality rate of adolescents in Panembong girang indirectly is the lack of control of adolescents in managing themselves. Often gather, in groups with peers, who incidentally have bad behavior. So that teenagers do what they should not do. Having an uncontrollable personality, causing the teenager to fall into drinking liquor or alcohol. One of the causes of death in adolescents worldwide due to accidents. in Panembong Girang the number of causes of death for adolescents is directly due to alcohol and accidents. The purpose of the study was to determine the cause of death of adolescents and to determine the lifestyle of panembong happy adolescents. The research method is a qualitative descriptive research design. The informants were taken by 3 neighbors next door to the meatball seller's house, teenagers and members of the Youth Organization. Results and Discussion: the cause of the death rate of adolescents due to alcohol died immediately and when drunk driving a motor vehicle an accident. Conclusion: the factors of the high mortality rate of adolescents in Panembong Girang are due to alcohol and accidents after drinking alcohol